Leadership Transformation in the Digital Age: Implications for Employee Performance and Engagement in Modern Organizations - Shafariah, Hanuna; Asril, Akmil; Agoestyowati, Redjeki (International Journal of Management Science and Information Technology, 2024)
Leadership transformation in the digital era has become a key element in determining the success of modern organizations. This study aims to analyze the effect of digital leadership on employee performance and engagement. A quantitative approach with descriptive and explanatory survey design was used to collect data from 200 respondents in the technology, banking, and education sectors. The research instrument was a 5-point Likert scale questionnaire measuring technological adaptability, support for innovation, policy flexibility, and information transparency as dimensions of digital leadership. The results of the linear regression analysis showed that digital leadership has a significant positive effect on employee performance with a regression coefficient of 0.45 (p
Keywords: Digital Leadership; Employee Performance; Employee Engagement; Technology Adaptability; Innovation; Information Transparency